Karakteristik Bayi Baru Lahir di RSUD dr. H. Chasan Boesoirie Ternate - Antoni, Emyherawati; Yati, Sri; Pratiwi, Dian (Mutiara: Multidiciplinary Scientifict Journal, 2025)
Newborns are babies who have just experienced the birth process, aged 0-28 days. According to data from the Indonesian Demographic and Health Survey (IDHS) in 2017, it shows a baby birth rate (AKB) of 24 per 1,000 live births. Every year newborn and neonatal deaths in the world account for 37% of all deaths in children under five. This study was an observational descriptive study. Based on the study, a total sample of 382 subjects was obtained. Male sex is 55.2%, birth weight in the range of 2500 - 4000 grams is 79.1%, birth length in the range of 48 - 52 cm is 69.4%, apgar score in the range of 7 - 10 is 92.6%, type of vaginal spontaneous delivery is 66.8%, gestational age is 37 - 42 weeks 86.6%. Based on the results of the study, it can be concluded that men are the most gender, the most birth weight is normal birth weight, the most birth length is normal body length, the highest apgar score is 7-10 (not asphyxia), the most types of labor are spontaneous vaginal, and the most gestational age is term pregnancy.